Subjective Outcome Evaluation Findings: Factors Related to the Perceived Effectiveness of the Tier 2 Program of the Project P.A.T.H.S. - Daniel T.L. Shek; Cecilia M.S. Ma (The Scientific World Journal)
After completion of the Tier 2 Program of the Project P.A.T.H.S. (Positive Adolescent Training through Holistic Social Programmes), 8,489 participants in 196 schools responded to the Subjective Outcome Evaluation Form (Form C) to assess their views of the program, program workers, and perceived effectiveness of the program. Four major program elements were identified, including programs based on the adventure-based counseling approach (n = 48), programs concentrated on volunteer training and services (n = 44), programs with both the adventure-based counseling approach and volunteer training activities (n = 63), and other programs with different foci (n = 41). Descriptive statistics showed that the respondents had positive perceptions of the program, workers, and benefits of the program. Perceived qualities of the program and the program workers were positively associated with perceived effectiveness of the program. Multiple regression analysis revealed that perceived qualities of the program, but not the program workers, predicted perceived effectiveness of the program. The theoretical and practical implications of the findings are discussed.